Transcriptional activity of vitamin D receptor in human periodontal ligament cells is diminished under inflammatory conditions. Issue 1 (21st June 2020) - Blufstein, Alice; Behm, Christian; Kubin, Barbara; Gahn, Johannes; Moritz, Andreas; Rausch‐Fan, Xiaohui; Andrukhov, Oleh
Abstract: Background: Although vitamin D3 deficiency is considered as a risk factor for periodontitis, supplementation during periodontal treatment has not been shown to be beneficial to date. Human periodontal ligament cells (hPDLCs) are regulated by vitamin D3 and play a fundamental role in periodontal tissue homeostasis and inflammatory response in periodontitis. The aim of this study is to investigate possible alterations of the vitamin D3 activity in hPDLCs under inflammatory conditions. Methods: Cells isolated from six different donors were treated with either 1, 25(OH)2 D3 (0 to 10 nM) or 25(OH)D3 (0 to 100 nM) in the presence and absence of ultrapure or standard Porphyromonas gingivalis lipopolysaccharide ( Pg LPS), Pam3CSK4, or interferon‐γ for 48 hours. Additionally, nuclear factor (NF)‐κB inhibition was performed with BAY 11‐7082. The bioactivity of vitamin D in hPDLCs was assessed based on the gene expression levels of vitamin D receptor (VDR)‐regulated genes osteocalcin and osteopontin. Additionally, VDR and CYP27B1 expression levels were measured. Results: The vitamin D3 ‐induced increase of osteocalcin and osteopontin expression was significantly decreased in the presence of standard Pg LPS and Pam3CSK4, which was not observed by ultrapure Pg LPS. Interferon‐y had diverse effects on the response of hPDLCs to vitamin D3 metabolites. NF‐kB inhibition abolished the effects of standard Pg LPS and Pam3CSK4. Standard Pg LPS and Pam3CSK4 increased VDR expression in the presence of vitamin D3 . CYP27B1 expression was not affected by vitamin D3 and inflammatory conditions. Conclusions: This study indicates that the transcriptional activity of VDR is diminished under inflammatory conditions, which might mitigate the effectiveness of vitamin D3 supplementation during periodontal treatment.